Kesadaran Multikultural dan Kewirausahaan Masyarakat Desa (Kasus Desa Wisata Batuan, Bali) - Solihin Solihin; Kanah Kanah (Bali Membangun Bali: Jurnal Bappeda Litbang, 2018)
Cultural tourism of Bali was supported by the existence of tourist objects or village activities, including the existence of the tourist village of Batuan, Sukawati, Gianyar that was flooded by tourists. This paper discusses the existence of tourist attraction at ‘Pura Batuan’ as multicultural education and growing entrepreneurship of the local people around the tourist object of “Pura Desa Batuan”. The research data was collected through observation, document study and interviews with 8 informants: visitor and top leader of Batuan Village and researcher of Balinese culture. Data analysis was carried out descriptively, qualitatively by applying stakeholder and cultural commodification theory. The results of the study show that the cultural heritage of Pura Desa Batuan had become part of the main tourist attraction in the tourist village of Batuan, Sukawati, Gianyar Regency which attracts tourists. Its existence has become a vehicle for multicultural education, strengthening the cultural traditions of the people and entrepreneurship of the Balinese people in the local village.